Assessing the effects of heavy metals and polycyclic aromatic hydrocarbons on benthic foraminifera: The case of Houshui and Yangpu Bays, Hainan Island, China - Zhang, Muhui; Yang, Chupeng; Cai, Guanqiang; Li, Shun; Nie, Xin; Zhou, Shuqin (Frontiers in Marine Science, 2023)
This work analyzed the distribution of benthic foraminiferal assemblages in Houshui and Yangpu Bays, Hainan Island, and assessed the relative effects of heavy metals, total organic carbon (TOC), and polycyclic aromatic hydrocarbons (PAHs) on foraminiferal assemblages. Organic matter was derived primarily from algae according to the C/N ratios, and PAHs were generated by petroleum and combustion of petroleum products, as inferred from the diagnostic ratios of PAH isomers. A total of 30 sites and 35 common species were classified into two groups of sites and two species groups using a two-way hierarchical cluster analysis. Sites were classified according to their geographical location (the bays). The relationship between benthic foraminifera and pollution was measured by canonical correspondence analysis (CCA). The effects of pollution on foraminiferal assemblages were observed in the following order: heavy metals > TOC > PAHs. The two species groups (I and II), which were divided by cluster analysis, were also identified by CCA. Species group I, consisting of agglutinated taxa including Bigenerina nodosaria, Ammobaculites agglutinans, Textularia spp., T. foliacea, Haplophragmoides canariensis and several tolerant species of hyaline forms including Ammonia beccarii, Elphidium advenum, E. hispidulum, Quinqueloculina laevigata and Q. seminula, was positively influenced by heavy metals; species group II, which was primarily composed of porcelaneous taxa (such as Massilina laevigata, Spiroloculina communis) and some hyaline taxa (E. crispum, and Elphidium spp.), was positively influenced by TOC and PAHs.